2020
DOI: 10.1186/s12886-020-01692-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retinal and choroidal variations in thyroid-associated ophthalmopathy using optical coherence tomography angiography

Abstract: Background To investigate the difference in retinal nerve fiber layer (RNFL) thickness, choroidal thickness (CT) and superficial retinal vessels between thyroid-associated ophthalmopathy (TAO) patients and healthy controls. To identify the potential influencing factors for these parameters and evaluate their diagnostic abilities in TAO. Methods Twenty active TAO patients, 33 inactive TAO patients and 29 healthy participants were enrolled. TAO patients were divided according to the clinical activity score (CA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
(51 reference statements)
0
23
0
6
Order By: Relevance
“…They observed that patients with TAO had significant changes in RNFL thickness, choroidal thickness and superficial retinal vessels. Patients with inactive TAO had greater retinal vascular density than healthy controls [21].…”
Section: Discussionmentioning
confidence: 84%
“…They observed that patients with TAO had significant changes in RNFL thickness, choroidal thickness and superficial retinal vessels. Patients with inactive TAO had greater retinal vascular density than healthy controls [21].…”
Section: Discussionmentioning
confidence: 84%
“…ONH vessel density and pRNFL thickness are measured by OCT-A and are useful in identifying TAO patients with DON, the most common vision-threatening condition in TAO and damaged optic nerves (23). It is reported that retinal nerve fiber layer thickness correlates with vascular density and the disease activity of TAO (1). Past studies show that altered fALFF in specific brain regions (left cuneus, bilateral superior frontal gyrus) correlates with RNFL thickness in patients with primary angle-closure glaucoma, suggesting that these finding are conducive to assessing the disease severity (16).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid-associated ophthalmopathy (TAO), commonly known as Graves' ophthalmopathy or thyroid eye disease, is an organspecific, progressive autoimmune inflammatory disease affecting the orbital. TAO is the commonest autoimmune orbital illness in adults (1,2) and often involves both orbits, with an asymmetrical appearance (3,4). The most common ophthalmic consequences in TAO patients are periorbital edema, upper eyelid retraction, diplopia, exophthalmos, dysfunctional eye movement, and impaired visual function (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have been focused on the retinal perfusion on TED patients to demonstrate early subclinical signs of the disease. [ 2 3 4 5 6 7 8 9 ] However, controversy exists as to whether the perfusion is decreased[ 2 3 ] or increased. [ 4 6 ] This discrepancy may be due to cross-sectional studies comparing the TED patients and controls, and also that vascular perfusion may vary based on the systemic condition of the patient, intraocular pressures (IOP), and inflammatory status of the orbit.…”
Section: Introductionmentioning
confidence: 99%